Severe hypertriglyceridemia in an adolescent female with diabetic ketoacidosis: A case report - Noopur N. Kulkarni; Bhakti U. Sarangi; Ajay A. Walimbe (Journal of Pediatric Critical Care)
Severe hypertriglyceridemia (SHT) is a rare metabolic complication of diabetic ketoacidosis (DKA) and may complicate the course by leading to acute pancreatitis. While intravenous insulin typically treats the dyslipidemia in these cases, the role of lipid-lowering agents to prevent adverse outcomes in patients not responding to insulin warrants further investigation. We report the case of an adolescent girl who presented to us with DKA and SHT (8639 mg/dL), requiring intravenous insulin as well as fibrates. She did not develop any complications that could be attributed to diabetic lipemia; investigations revealed no sequelae of hyperlipidemia or evidence of familial dyslipidemia.